(untitled) (Journal of Engineering, 2007)
The static characteristics of porous floating ring journal bearing under hydrodynamic lubrication condition when operating with an improved boundary conditions are theoretically analyzed. An isothermal finite bearing theory was adopted during this analysis. The effect of different parameters, namely, permeability, geometrical dimensions of the ring and the bearing are considered. It was assumed that oil is supplied through the outside diameter of the bearing under low supply pressure. The angular extent of the oil – film formed in journal – ring and ring – bearing oil films was obtained by applying the integral momentum equation at the leading edge of the oil – film to define the beginning of the oil extent. While, the continuity of flow across the trailing edge was used to define the end of the oil extent. Numerical results show that the bearing performance affected by different parameters namely, permeability, eccentricity ratios of inner and outer oil – film, the clearance ratios, and the radii ratios.